2020
DOI: 10.1371/journal.pone.0240346
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and socioeconomic characteristics predict COVID-19 mortality and resource utilization in Brazil

Abstract: Background Given the severity and scope of the current COVID-19 pandemic, it is critical to determine predictive features of COVID-19 mortality and medical resource usage to effectively inform health, risk-based physical distancing, and work accommodation policies. Non-clinical sociodemographic features are important explanatory variables of COVID-19 outcomes, revealing existing disparities in large health care systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 28 publications
5
43
0
5
Order By: Relevance
“…The fact that males with no underlying comorbidity or disease also tend to have higher death risk than females as age progresses also reinforces the findings of an asymmetric impact of COVID-19 in regards to sex and is consistent with previous studies' results [1][2][3][4][5]. A possible explanation provided in [5], regarding male infectiousness, relates to smoking and higher circulating angiotensin converting enzyme 2 (ACE2) levels in men, SARS-CoV-2 utilizes ACE2 receptors found at the surface of the host cells to get inside the cell, this is also an important factor in specific underlying comorbidities or diseases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The fact that males with no underlying comorbidity or disease also tend to have higher death risk than females as age progresses also reinforces the findings of an asymmetric impact of COVID-19 in regards to sex and is consistent with previous studies' results [1][2][3][4][5]. A possible explanation provided in [5], regarding male infectiousness, relates to smoking and higher circulating angiotensin converting enzyme 2 (ACE2) levels in men, SARS-CoV-2 utilizes ACE2 receptors found at the surface of the host cells to get inside the cell, this is also an important factor in specific underlying comorbidities or diseases.…”
Section: Discussionsupporting
confidence: 91%
“…Different studies have identified age group, sex and underlying comorbidity or disease as critical factors for disease severity and mortality risk [1][2][3][4][5]. In the current work, we use these three factors as feature variables in machine learning models for extracting a profile for COVID-19 death probability, conditional on these three risk factors, using the US Centers for Disease Control and Prevention (CDC)'s COVID-19 case surveillance data sample 1 which contains a large sample of COVID-19 confirmed cases with records for these three factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Israeli healthcare system is universal and mandates all citizens to join one of the official non-profit health insurance organizations. Regional 11 or financial 12 disparities affecting the availability of health-care resources in other countries as well as racial variation 13 may affect COVID-19-related mortality. Future studies should be conducted in order to determine if this effect is also observed in other countries with different healthcare systems, and the specific threshold of patients representing healthcare capacity in each healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…[21] In Brazil, income and education inequalities were positively associated with COVID-19 incidence and mortality rates. [22,23] Our results showed that living in areas of very low or low SES is associated with higher COVID-19 mortality risk with a consistent dose-response effect pattern. These results are consistent with a previous report of inequalities in mortality by SES levels among COVID-19 confirmed cases in Bogotá.…”
Section: Discussionmentioning
confidence: 53%